Seasonal Characteristics, Sources and Pollution Pathways of PM10 at High Altitudes Himalayas of India - Nikki Choudhary; Priyanka Srivastava; Monami Dutta; Sauryadeep Mukherjee; Akansha Rai; Jagdish Chandra Kuniyal; Renu Lata; Abhijit Chatterjee; Manish Naja; Narayanasamy Vijayan; Tuhin Kumar Mandal; Sudhir Kumar Sharma (Aerosol and Air Quality Research)
Abstract The present study represents the annual and seasonal concentration of PM10 over different sites (Darjeeling, Nainital, Mohal-Kullu) across the Himalayan region of India from July 2018 to December 2019. The collected PM10 samples were analyzed for carbonaceous aerosols [organic carbon (OC), elemental carbon (EC), water-soluble organic carbon (WSOC), primary organic carbon (POC), secondary organic carbon (SOC)] and major trace elements to inspect their possible sources. The annual average concentrations of PM10 over Mohal-Kullu, Nainital, and Darjeeling were recorded as 57 ± 32 µg m–3, 65 ± 41 µg m–3, and 54 ± 17 µg m–3, respectively. The high OC/EC ratio and significant correlation of OC with EC and WSOC with OC indicated a significant effect of biomass burning aerosols over the study sites. Principal component analysis/absolute principal component score (PCA/APCS) resolved four major sources: crustal/soil dust (26.6%), biomass burning/fossil fuel combustion (28%), vehicular emissions (28%), and industrial emissions/coal combustion (17%). Identification of the source region using the potential source contribution function (PSCF) and concentration weighted trajectories (CWT) showed that PM10 was mainly transported from the northwestern part of India (Haryana, Punjab), the northeastern region of Pakistan, the Thar Desert, and Indo-Gangetic Plain (IGP), which contributed to dust-related aerosols over the Himalayan region of India.